2013
DOI: 10.1002/wrna.1215
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of flowering time in annual and perennial plants

Abstract: Flowering time plays a significant role in the reproductive success of plants. So far, five major pathways to flowering have been characterized in Arabidopsis, including environmental induction through photoperiod, vernalization, and gibberellins and autonomous floral iation, and aging by sequentially operating miRNAs (typically miR156 and miR172) responding to endogenous cues. The balance of signals from these pathways is integrated by a common set of genes (FLOWERING LOCUS C, FLOWERING LOCUS T, LEAFY, and SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
138
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 100 publications
(185 reference statements)
0
138
0
Order By: Relevance
“…Tropical lines flower under shortday (SD) conditions and depend on photoperiods to flower (Colasanti and Coneva, 2009). Especially in temperate maize lines, endogenous signals related to the developmental stage of the plant appear to play the main role in floral induction, like the autonomous, the aging, and the GA 3 signaling pathways (for review, see Khan et al, 2014).Most information about factors controlling the transition from the vegetative to the floral phase was gained from research with the LD-adapted model plant Arabidopsis. It was demonstrated that the different signaling pathways mediating both environmental and endogenous cues converge at a few floral integrators (for an overview of this complex network in Arabidopsis, see Blümel et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical lines flower under shortday (SD) conditions and depend on photoperiods to flower (Colasanti and Coneva, 2009). Especially in temperate maize lines, endogenous signals related to the developmental stage of the plant appear to play the main role in floral induction, like the autonomous, the aging, and the GA 3 signaling pathways (for review, see Khan et al, 2014).Most information about factors controlling the transition from the vegetative to the floral phase was gained from research with the LD-adapted model plant Arabidopsis. It was demonstrated that the different signaling pathways mediating both environmental and endogenous cues converge at a few floral integrators (for an overview of this complex network in Arabidopsis, see Blümel et al, 2015).…”
mentioning
confidence: 99%
“…Tropical lines flower under shortday (SD) conditions and depend on photoperiods to flower (Colasanti and Coneva, 2009). Especially in temperate maize lines, endogenous signals related to the developmental stage of the plant appear to play the main role in floral induction, like the autonomous, the aging, and the GA 3 signaling pathways (for review, see Khan et al, 2014).…”
mentioning
confidence: 99%
“…The results of these studies illuminate the similarities and differences between and among long-and short-day plants (Shrestha et al 2014;Zheng et al 2009;Hayama and Coupland 2004). Photoperiodic induction of flowering in annual and perennial plants is discussed by Khan et al (2014).…”
Section: The Various Pathwaysmentioning
confidence: 95%
“…Whether the autonomous or the environment-reactive pathway prevails in flower induction, depends on the plants and varies a lot (Aukerman and Amasino 1996). There is furthermore a gibberellin pathway (Khan et al 2014;Coelho et al 2013). …”
Section: The Various Pathwaysmentioning
confidence: 98%
“…For example, in the model plant Arabidopsis thaliana, four major flowering pathways have been identified: the photoperiod pathway, the vernalization pathway, the autonomous pathway and the gibberellin (GA) pathway (Jack 2004;Corbesier and Coupland 2006). Most recently, an endogenous pathway by Communicated (Srikanth and Schmid 2011;Khan et al 2014). Genetic and molecular analyses have identified a large number of genes that respond to various signaling pathways and participate in the regulation of flowering, and the crosstalk between pathways constitutes a complex network of flowering via floral integrator genes (Srikanth and Schmid 2011;Khan et al 2014).…”
Section: Introductionmentioning
confidence: 97%